Correction: Lencwe et al. An Effective Control for Lead-Acid Performance Enhancement in a Hybrid Battery-Supercapacitor System Used in Transport Vehicles. Sustainability 2021, 13, 13971 - Lencwe, Mpho J.; Chowdhury, S. P. Daniel; Olwal, Thomas O. (Sustainability, 2023)
The authors would like to make the following corrections about the published paper [...]